Kesejahteraan Petani Garam di Kabupaten Sumenep Madura (Analisis dengan Pendekatan Maqasid Shariah) - Firman Setiawan (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
As a country surrounded by oceans, Indonesia has huge potential in salt production, and Sumenep district is one of the districts with the largest salt production in Indonesia. However, the potential and large production results are not in accordance with the economic conditions of salt farmers. This is due to several things, one of which is because the selling price of salt is not in accordance with the HPP (Harga Pembelian Pemerintah) as well as guidance and assistance to increase the productivity of salt farmers who are lacking. This problem will have an impact on the welfare of salt farmers. This study aims to determine how the level of welfare of salt farmers in Sumenep district in the perspective of maqashid al-shari'ah. This research was examined with descriptive qualitative methods. The data was collected through semi-structured interviews with salt farmers in Sumenep district, then analyzed using the maqashid al-shari'ah approach. Thus, the level of welfare of salt farmers is measured in five aspects of maqashid al-shari'ah; hifz al-din (guarding religion), hifz al-nafs (guarding life), hifz al-'aql (guarding thoughts), hifz al-nasl (guarding nasab) , and hifz al-mal (protect wealth). The results of this study are the welfare of salt farmers from the aspects of hifz al-din and hifz al-naslhave been achieved (prosperous), but from the aspects of hifz al-nafs, hifz al- 'aql, and hifz} al-mal has not been reached (not prosperous).